Catalytic enantioselective addition of isocyanoacetate to 3-methyl-4-nitro-5-styrylisoxazoles under phase transfer catalysis conditions. Issue 43 (7th October 2015) - Disetti, Paolo; Moccia, Maria; Salazar Illera, Diana; Suresh, Surisetti; Adamo, Mauro F. A.
Abstract : The reaction between 3-methyl-4-nitro-5-styrylisoxazoles and ethyl isocyanoacetate proceeded under PTC to give enantioenriched monoadducts in high ee (up to 99%). Abstract : The reaction between 3-methyl-4-nitro-5-styrylisoxazoles and ethyl isocyanoacetate proceeded under phase transfer catalysis to give enantioenriched monoadducts in high enantiomeric excess (up to 99% ee). The resulting adducts were subsequently cyclised to give 2, 3-dihydropyrroles and substituted pyrrolidines in identical high ees and as a single diastereoisomer.